Genotypes and phenotypes of protein S deficiency in Thai children with thromboembolism - Patcharee Komwilaisak (2018)
© 2016 Wiley Periodicals, Inc. The prevalence of protein S (PS) deficiency in Asian patients with venous thromboembolism is around 8–30%, higher than that in Caucasian populations. The present study reports the genotypes (including one novel mutation) and phenotypes of children with PS deficiency at a tertiary care institute. A total of six patients were included, three with arterial ischemic stroke, two with cerebral venous sinus thrombosis, and one with deep vein thrombosis. PS mutations were identified in four patients: p.R355C, p.G336D, p.E67A, and p.N188KfsX9. p.N188KfsX9 is a novel mutation with less than 20% PS activity noted in heterozygotes.